BAJOCIAN LISSOCERATINAE (HAPLOCERATOIDEA, AMMONITIDA) FROM THE MEDITERRANEAN-CAUCASIAN SUBREALM (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
A revision of the Bajocian Lissoceratinae is presented. The study of a huge quantity of lissoceratins from different sites of the Western Tethys (Northwest European, Sub-Mediterranean and Mediterranean bioprovinces) within the Tethys-Panthalassa Realm provided data useful to implement the systematics of these almost neglected, never deeply analysed ammonites. Two genera, Lissoceras Bayle and Semilissoceras n. gen., are described with 16 species, among which 8 (four dimorphic, three macroconchiate and one microconchiate) new species: L. submediterraneum, L. maizetense, L. ovale, L. sturanii, L. maerteni, S. ellipticum, S. turgidulum and S. costellatum. The neotype of L. oolithicum is established. The microconchiate genus Microlissoceras is regarded as the junior synonym of the macroconchiate Lissoceras. Taxa are discussed according to four groups that gather taxa sharing common morpho-structural features. They roughly relate to successive biochronostratigraphical intervals within the Bajocian Stage and are headed by species largely known in literature: S. semicostulatum (Buckman) with suboval to compressed whorl section and rectiradiate ribs on the outer half flank; L. oolithicum (d’Orbigny) with subtriangular to ovate whorl section, large and depressed ventral saddle, large suspensive lobe; L. haugi Sturani with ovate to globular whorl section, narrow lobe E and suspensive lobe; and L. psilodiscus (Schloenbach) with highly compressed whorl section, high ventral saddle and narrow lobe E. The phyletic relation of Lissoceras and Semilissoceras to the Aalenian-Bajocian Bradfordia-group is discussed, regarding Semilissoceras as the known stem-taxon on which the subfamily Lissoceratinae bases.